RELATIONSHIP OF PEER SUPPORT AND PHYSICAL ACTIVITY AMONG ADOLESCENTS IN A PUBLIC ISLAMIC HIGH SCHOOL IN THE DISTRICT OF ACEH BESAR - Amanda, Putri; Asniar, Asniar; R, Farah Dineva (NURSE: Journal of Nursing and Health Science, 2024)
Background: Lack of physical activity is a risk factor for various chronic diseases that must be prevented with health promotion interventions. In designing targeted interventions, it is necessary to study health determinants that can increase the success of an intervention. In the adolescent age group, one of the determinants of physical activity is social support from peers, which impacts increasing physical activity. This study aims to determine the relationship between peer support and physical activity among adolescents at Public Islamic High School in Aceh Besar. Method: The research method used is a correlative with a cross-sectional approach. One hundred nine respondents were involved in this study and selected by a simple random sampling technique. Data was collected using the Social Support for Exercise Scale and Physical Activity Questionnaire-Adolescents (PAQ-A) and analyzed using the Chi-Square test. Results: The data analysis results show a significant relationship between peer support and adolescents' physical activity at Public Islamic High School in Aceh Besar (p-value 0.002). This research shows that if teenagers have good social support from their peers, they can increase their physical activity. Conclusion: For this reason, it is recommended that community nurses be able to design interventions that facilitate peer support for adolescents in carrying out physical activities. Collaboration between various stakeholders, including parents, school administrators, and related stakeholders, is needed to create an atmosphere and facilities conducive to adequate peer support for teenagers.